The power of belief? Evidence of reduced fear extinction learning in Catholic God believers - Carmelo Mario Vicario; Laura Culicetto; Chiara Lucifora; Francesca Ferraioli; Simona Massimino; Gabriella Martino; Francesco Tomaiuolo; Alessandra Maria Falzone (Frontiers in Public Health)
Religious beliefs can shape how people process fear. Yet the psychophysiological mechanisms underlying this phenomenon remain poorly understood. We investigated fear learning and extinction processes in a group of individuals who professed a belief in God, compared to non-believers. Using a virtual reality Pavlovian fear conditioning/extinction task, we measured neurovegetative activity associated with these forms of associative learning. Our finding shows reduced fear extinction among God believers, compared to non-believers. This suggests that the general mechanism of fear extinction learning is suppressed in these individuals. Importantly, this effect was not explained by state or trait anxiety scores. These findings align with previous evidence linking religiosity and spirituality with the neural circuit of fear and suggest that religiosity may be associated with weaker inhibitory learning processes related to fear.